A randomized controlled add-on trial of fluoxetine and cognitive behavioral therapy for help-seeking men with a sexual interest in children: presentation of the PARACHUTES trial protocol and initial feasibility data - Adebahr, Roberth; Görts Öberg, Katarina; Rahm, Christoffer; Byström, Markus; Sparre, Charlotte; Desai Boström, Adrian E.; Bottai, Matteo; Jokinen, Jussi; Savard, Josephine (Frontiers in Psychiatry, 2024)
Sexual Interest in Children (SIC) is a major risk factor for sexual offending, yet clinical trials are sparse. The present protocol outlines a randomized controlled trial (RCT) that aims to investigate the effectiveness of fluoxetine and Cognitive Behavioral Therapy (CBT) in helpseeking men with SIC. Methods Adult men contacting the Swedish telephone helpline PrevenTell are screened for inclusion and invited to further assessment on site. One hundred and eleven men with SIC (defined as DSM-5 pedophilic disorder or hebephilia) will be randomized (1:1:1 ratio) to receive one of three interventions for 14 weeks: (1) an internet-administered psychoeducational program (iPP), ( 2) iPP and the addition of fluoxetine 20-40 mg or (3) iPP and the addition of internet-administered CBT (iCBT). Exclusion criteria include severe psychiatric illness, contraindicating treatment and an elevated risk of committing hands-on sexual offences. Symptom intensity is assessed at baseline, pre-treatment, every other week for 12 weeks, and post treatment. The primary outcome measure is the Sexual Interest in Children: Current Assessment Scale (SIC: CAS) that quantifies sexual behaviors associated with SIC as well as perceived distress and impairment. Secondary outcomes include measures of dynamic risk-factors for committing sexual offences.The data collected during the initial 20 months of recruitment were analyzed to predict the required number of individuals to be screened and estimate the probable length of the data collection phase. As of March 2022 to November 2023, 146 men have called PrevenTell and disclosed a sexual interest in minors. Following pre-screening, 110 men were excluded from participation in the trial. Current SSRI therapy was the primary reason for exclusion (n = 24; 22%), followed by an elevated risk of committing hands-on sexual offences (n = 14; 13%). Amongst the 31 men who underwent the screening procedure on site, 26 were allocated to either iPP, iPP+fluoxetine, or iPP+iCBT. The recruitment rate indicates that the trial will be concluded within the pre-estimated timeframe. Discussion This is the first RCT of treatment with SSRI and iCBT in a population of help-seeking men with SIC. The significance of this trial and its methodological strengths and limitations are discussed.